The relationship between the effectiveness professional development programme of teaching and learning and competency of instructional supervision of technical and vocational senior teachers of secondary schools in Kuala Lumpur and Selangor - Hassan, Aminuddin; Awi, Asnaini (Universiti Putra Malaysia Press, 2016)
This study aims to identify the relationship between the effectiveness of professional development programme in teaching and learning and the level of competency of instructional supervision of Technical and Vocational Senior Teachers (TVSTs) in secondary schools in Kuala Lumpur and Selangor. Questionnaires for TVSTs were distributed to 200 TVSTs for collecting the quantitative data to be analysed. The findings showed that there exists a positive significant relationship between the level of effectiveness of professional development programme in teaching and learning (r= .51, p ≥ .05) and the TVSTs’ competency level in instructional supervision. The findings also suggested that the instructional supervision training in technical and vocational teaching should be held for TVST. Finally, all the problems faced by TVSTs and their suggestions need to be taken into considerations by responsible parties in order to find solutions to the real factors based on instructional supervision competency in the secondary schools in Kuala Lumpur.